KEDUDUKAN DAN PERAN PEMBANTU PEGAWAI PENCATAT NIKAH (P3N) DALAM URUSAN PERNIKAHAN: (Studi Kasus di Wilayah KUA Kecamatan Palu Selatan Kota Palu) - Ilmiati Ilmiati; Uswatun Hasanah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2017)
Through the Instruction of the Director General of Islamic Guidance No. DJ.II / I Year 2015 on the Appointment of Assistant Employee of Marriage Recorders (P3N), the task of P3N is abolished and to hand over the affairs of marriage to the full responsibility of the Head of Office of Religious Affairs. But in fact, people still need the existence of P3N in helping the affairs of marriage